Comparing topical anaesthesia, local cooling and vibration technique as pain control during palatal local anaesthetic injection - Aziz, Nur Izzati; Abdul Rahman, Bibi Dayana; Subramaniam, Pram Kumar; Ismail, Izzati Nabilah Ismail (2019)
Introduction: It is ironic that local anaesthesia (LA) is essential in providing painless dentistry when LA injection itself is often considered as being a most painful experience. Numerous techniques have been proposed to reduce pain on injection such as topically applied anaesthetic, vibration, buffered local anaesthesia and local cooling. Aims and Objectives: This study aims to determine whether local cooling and vibration onto the injection site are superior techniques in relieving pain of injection compared to topical anaesthesia application. Methodology: 20 adults received three methods of pain control namely topical anaesthesia, local cooling and vibration prior to palatal LA injection. Subjects recorded their responses via the Visual Analogue Scale(VAS), Numerical Rating Scale(NRS) for pain score and State Trait Anxiety Inventory-6(STAI-6) for anxiety score before and after injection following each application method. Results: Local cooling and vibration method yielded less actual pain during palatal injection based on NRS and VAS compared to its anticipated pain though statistically non-significant (p>0.05). Similarly, ANOVA comparison revealed that mean pain score for NRS and VAS is non-significantly lowest for local cooling method followed by vibration and topical anaesthesia. Additionally, subjects aged 31-45 years old had experienced the least pain during injection with local cooling and vibration application. Interestingly, patients felt less anxious during injection after receiving topical anaesthesia compared to local cooling and vibration. Conclusion: During palatal local anaesthetic injection, vibration and local cooling had proven to be much effective in reducing pain compared to application of topical anaesthesia. (244 words) Keywords : Vibration, Local Cooling, Topical anaesthesia, Palatal injection